Interconnection transmission lines out-of-step protection based on electrical power derivative - Canahua, Raúl Eduardo Farfán (2025)
Most existing out-of-step protection (OOSP) schemes are designed to protect synchronous generators. However, when the electrical center is located within the transmission system, these schemes may experience delays or fail to detect the phenomenon, rendering them ineffective for interconnected transmission lines. This research proposes an adaptation of the method based on the derivative of electrical power, initially developed for synchronous generators, for application in transmission lines near the electrical center. This method was chosen due to its ability provide coordination with other protection schemes, and to eliminate the constant component of electrical power caused by the proximity of large constant power loads. The adaptation was developed to overcome the limitations of the original method and incorporates additional contributions, such as a formula to adjust the power derivative threshold based on analytical expressions of active and reactive power, and a novel strategy to distinguish between stable and unstable oscillations. Validations were carried out through simulations in the EMTP/ATP software, using its ATPDraw interface, covering various fault scenarios and operating conditions. The simulations demonstrated that the adapted method resolves the identified limitations and ensures efficient coordination between the stages of OOSP in the studied system, in accordance with the philosophy that transmission line protections should act first, while generator protections should act last. The study confirmed the practical feasibility of the adapted method in real systems, establishing it as a reliable and efficient alternative for protecting transmission lines against out-of-step conditions.